Mitral endocarditis due to Rothia aeria with cerebral haemorrhage and femoral mycotic aneurysms, first French description. (September 2016) - Collarino, R.; Vergeylen, U.; Emeraud, C.; Latournèrie, G.; Grall, N.; Mammeri, H.; Messika-Zeitoun, D.; Vallois, D.; Yazdanpanah, Y.; Lescure, F.-X.; Bleibtreu, A.
Abstract: Rothia aeria is a Rothia species from the Micrococcaceae family. We report here the first French R. aeria endocarditis complicated by brain haemorrhage and femoral mycotic aneurysms. Altogether, severity and antimicrobial susceptibility should make us consider the management of R. aeria endocarditis as Staphylococcus aureus methicillin-susceptible endocarditis.